The Delft Sand, Clay and Rock Cutting Model - S.A. Miedema (IOS Press, 2014)
Sand, clay and rock have to be excavated for a variety of purposes, such as dredging, trenching, mining (including deep sea mining), drilling, tunnel boring and many other applications. Many excavations take place on dry land, but they are also frequently required in completely saturated conditions, and the methods necessary to accomplish them consequently vary widely. This book provides an overview of cutting theories. It begins with a generic model, valid for all types of soil (sand, clay and rock), and continues with the specifics of dry sand, water-saturated sand, clay, atmospheric rock and hyperbaric rock. Small blade angles and large blade angles are discussed for each soil type, and for each case considered the equations/model for cutting forces, power and specific energy are given. With models verified by laboratory research, principally from the Delft University of Technology, and data from other recognized sources, this book will prove an invaluable reference for anybody whose work involves major excavations of any kind.